Contributions of Loss Events to Loss Distress and Trauma Symptoms in Recently Resettled Refugee Women at Risk. Issue 4 (19th May 2017) - Vromans, Lyn; Schweitzer, Robert D.; Brough, Mark; Correa-Velez, Ignacio; Murray, Kate; Lenette, Caroline
ABSTRACT: This research examined contributions of loss events to loss distress and trauma symptoms (accounting for trauma events) for refugee women at risk. Participants ( N = 104) responded to the Multidimensional Loss Scale (loss events and distress) and Harvard Trauma Questionnaire (trauma events and symptoms). Loss events contributed uniquely to loss distress (explaining additional 50.8% variance), and made a unique contribution to trauma symptoms (explaining additional 5.2% variance) approximately equal to trauma events. Appropriate response to psychic distress in refugee women at risk requires assessment of both loss and trauma and consideration of cultural differences in ways loss is expressed and meaning ascribed to symptoms.